Development and Preliminary Analysis of a VLF-Band Electromagnetic-Wave Observation System for Short-Term Earthquake Precursory Monitoring - Nagao, Toshiyasu; Kamogawa, Masashi; Izutsu, Jun; Suzuki, Tomoyuki; Saito, Airi; Sugiura, Shigeki; Kondo, Hitoshi (Frontiers in Earth Science, 2021)
It has been known that the preseismic VLF pulse-like electromagnetic signals sometimes increases a few days before the sizable earthquakes especially inland earthquakes. More than two decades ago, the Tokai University group developed a digital recording system and published remarkable results. However, at the time, due to the limitation of personal computer’s data storage and CPU power, they quitted the observation. Therefore, we re-started the research by using the current technology. Fortunately, the “Japanese National Earthquake Prediction Research Project” by the Ministry of Education, Culture, Sports, Science and Technology (MEXT) decided to support our proposal. This is a preliminary report of the development of the new observation system and preliminary results. In this paper, we introduce an electromagnetic wave arrival discrimination algorithm that combines the autoregressive (AR) model and the Akaike Information Criterion (AIC), which are commonly used for automatic waveform reading in seismology, to obtain more detailed arrival times of electromagnetic waves. Then, the source decision was tried using arrival time difference (TDOA - Time Difference of Arrival) of the electromagnetic wave. As a result, several electromagnetic pulses near the epicenter were observed 2 days before the largest inland earthquake (M = 5.6) occurred near the observation network during the observation period. At the present time, these pulses cannot be definitively identified as precursory phenomena, but they are the encouraging result of future observations.